Unit lengths

Geometry Level pending

On equilateral A B C \triangle ABC , point D D lies on B C BC a distance 1 1 from B B , point E E lies on A C AC a distance 1 1 from C C , and point F F lies on A B AB a distance 1 1 from A A . Segments A D AD , B E BE , and C F CF intersect in pairs at points G G , H H , and J J which are the vertices of another equilateral triangle. The area of A B C \triangle ABC is twice the area of G H J \triangle GHJ . The side length of A B C \triangle ABC can be written r + s t \frac{r+\sqrt{s}}{t} , where r r , s s , and t t are relatively prime positive integers. Find r + s + t r + s + t .


The answer is 30.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let the position coordinates of A , B , C A, B, C be ( a 2 , a 3 2 ) , ( 0 , 0 ) , ( a , 0 ) (\frac{a}{2},\frac{a\sqrt 3}{2}), (0,0), (a, 0) respectively. Then those of D , E , F D, E, F are ( 1 , 0 ) , ( 2 a 1 2 , 3 2 ) , ( a 1 2 , 3 ( a 1 ) 2 ) (1,0), (\frac{2a-1}{2}, \frac{\sqrt 3}{2}), (\frac{a-1}{2}, \frac{\sqrt 3(a-1)}{2}) respectively. Equations of B E , C F , A D \overline {BE},\overline {CF},\overline {AD} are y = 3 2 a 1 x , y = 3 ( 1 a ) 1 + a ( x a ) , y = 3 a a 2 ( x 1 ) y=\frac{\sqrt 3}{2a-1}x, y=\frac{\sqrt 3(1-a)}{1+a}(x-a), y=\frac{\sqrt 3a}{a-2}(x-1) respectively. Solving we get the position coordinates of G , H G, H as ( a ( 2 a 1 ) 2 ( a 2 a + 1 ) , a 3 2 ( a 2 a + 1 ) ) (\frac{a(2a-1)}{2(a^2-a+1)}, \frac{a\sqrt 3}{2(a^2-a+1)}) and ( a ( a 1 ) ( 2 a 1 ) 2 ( a 2 a + 1 ) , 3 a ( a 1 ) 2 ( a 2 a + 1 ) ) (\frac{a(a-1)(2a-1)}{2(a^2-a+1)}, \frac{\sqrt 3a(a-1)}{2(a^2-a+1)}) . So, G H = a 2 ( a 2 ) 2 ( 2 a 1 ) 2 + 3 a 2 ( a 2 ) 2 4 ( a 2 a + 1 ) 2 = a ( a 2 ) a 2 a + 1 |\overline {GH}|=\sqrt {\frac{a^2(a-2)^2(2a-1)^2+3a^2(a-2)^2}{4(a^2-a+1)^2}}=\frac{a(a-2)}{\sqrt {a^2-a+1}} . By the given condition of the problem, a 2 = 2 × a 2 ( a 2 ) 2 a 2 a + 1 a 2 7 a + 7 = 0 a = 7 + 21 2 a^2=2\times \frac{a^2(a-2)^2}{a^2-a+1}\implies a^2-7a+7=0\implies a=\frac{7+\sqrt {21}}{2} . Hence r = 7 , s = 21 , t = 2 r=7, s=21, t=2 and r + s + t = 30 r+s+t=\boxed {30} .

nice solution sir!

nibedan mukherjee - 1 year, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...